2022
DOI: 10.3390/ma15082957
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructural Characterization of Metakaolin Geopolymers Based on Orthogonal Tests

Abstract: Metakaolin was used as a raw material for the preparation of geopolymers, where two types of alkali activators (Na2SiO3 + NaOH and Na2SiO3 + NaOH) were used to prepare metakaolin geopolymers at room temperature. The mechanical properties and microstructures of the metakaolin geopolymers were analyzed. A three-factor, four-level orthogonal test was designed to investigate the mechanical properties of the metakaolin geopolymer with different ratios. The compressive and flexural strength of different specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…By introducing the method of orthogonal experimental design and using the "orthogonal table" to arrange the multi-factor experimental schemes, the intrinsic essential laws contained in a large number of schemes are reflected by a limited number of typical and representative schemes, and the influence trend, primary and secondary order, and the significance degree of parameters on cumulative yield can be quantitatively determined (Zeng et al, 2012). In addition, an orthogonal test can eliminate part of the interference caused by test errors and the results are easy to analyze (Dai et al, 2022).…”
Section: Optimizing Construction Parameters 2331 Orthogonal Experimen...mentioning
confidence: 99%
“…By introducing the method of orthogonal experimental design and using the "orthogonal table" to arrange the multi-factor experimental schemes, the intrinsic essential laws contained in a large number of schemes are reflected by a limited number of typical and representative schemes, and the influence trend, primary and secondary order, and the significance degree of parameters on cumulative yield can be quantitatively determined (Zeng et al, 2012). In addition, an orthogonal test can eliminate part of the interference caused by test errors and the results are easy to analyze (Dai et al, 2022).…”
Section: Optimizing Construction Parameters 2331 Orthogonal Experimen...mentioning
confidence: 99%
“…(c, d) Adapted with consent under the terms of the CC-BY 4.0 license. [41] Copyright 2022, The Authors. (e, f) Adapted with permission.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Qiu et al [ 9 ] revealed that high OH - concentrations in the activator caused cementitious building materials to lose strength. Dai et al [ 10 ] investigated the effect of activator type on the properties of geopolymers by preparing geopolymers with two different activators, NaOH and KOH. The results showed that the KOH-based geopolymer had better mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ouda et al [ 18 ] focused on the thermal stability and resistance to seawater immersion of fly ash geopolymers doped with various percentages of tile waste compared to normal blends, and showed that the addition of 10% tile waste enhanced the compressive strength and microstructural properties both before and after exposure to seawater solution. Dai et al [ 10 ] investigated the effect of activator type on the properties of geopolymers by preparing geopolymers with two different activators, NaOH and KOH. The results showed that the KOH-based geopolymer had better mechanical properties.…”
Section: Introductionmentioning
confidence: 99%